Audit Information Technology Based on COSO ERM Framework (Case Study: Dikpora of XYZ City) - Wahyudin, Wahyudin; Maricar, M. Azman; Wijaya, I Wayan Arta (International Journal of Engineering and Emerging Technology, 2017)
Information Technology utilization as support of the achievement of the goal and objectives of the organization must be balanced with the effectiveness and efficiency of its management. Thus the audit of IT must be done to maintain the security of information systems as the assets of the organization to maintain the integrity of the information stored and processed and of course to improve the effectiveness of the use of information technology and supports the efficiency in the environment of the organization. This research goal to perform the mapping of IT audit stage along with the controls and then applied on an organization, namely Dikopra of XYZ City to view the performance of existing IT. The framework is used as a reference is COSO ERM. The audit event is done by using the phases that exist on the wizard on the COSO ERM which is divided into several components. The results of the evaluation or done analysis of root cause so we can get a recommendation for a better IT management again.